Broadway bounty [large type] - Randisi, Robert J. (Wheeler Publishing large print Western, 2010)
When a fellow bounty hunter is gunned down, Decker wants retribution. Leaving Harrison City, Iowa, and heading for New York City armed with the names of the killers, Decker is bent on evening the score but instead is mistaken for his murdered colleague. Dodging bullets in a place unknown to the Bounty Hunter and feeling more vengeful than ever, Decker is driven to a riveting showdown in Central Park before he can let his guns cool off.